2011
DOI: 10.1186/1471-2407-11-208
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 SNP309, gene-gene interaction, and tumor susceptibility: an updated meta-analysis

Abstract: BackgroundThe tumor suppressor gene p53 is involved in multiple cellular pathways including apoptosis, transcriptional control, and cell cycle regulation. In the last decade it has been demonstrated that the single nucleotide polymorphism (SNP) at codon 72 of the p53 gene is associated with the risk for development of various neoplasms. MDM2 SNP309 is a single nucleotide T to G polymorphism located in the MDM2 gene promoter. From the time that this well-characterized functional polymorphism was identified, a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 74 publications
2
45
0
Order By: Relevance
“…10 Studies have shown that a Single Nucleotide Polymorphism (SNP) on promoter region of MDM2 gene, the SNP309 (T to G change on nucleotide 309 of the first intron), results in a higher level of MDM2 mRNA and MDM2 protein, and consequent reduction of the p53 pathway. 11 The SNP309 occurs at a relatively high frequency in the general population, and it was shown that it presents a strong association with HPVmediated cervical carcinogenesis. 12 Based on the presented data, this study aimed to investigate the HPV infection spectrum, to identify the most prevalent genotypes, to determine the frequencies of SNPs Arg72Pro and MDM2 SNP309, and their association with possible risk factors for viral persistence and for the development of pre-neoplastic and neoplastic lesions of the uterine cervix in HIV-infected women.…”
Section: Introductionmentioning
confidence: 99%
“…10 Studies have shown that a Single Nucleotide Polymorphism (SNP) on promoter region of MDM2 gene, the SNP309 (T to G change on nucleotide 309 of the first intron), results in a higher level of MDM2 mRNA and MDM2 protein, and consequent reduction of the p53 pathway. 11 The SNP309 occurs at a relatively high frequency in the general population, and it was shown that it presents a strong association with HPVmediated cervical carcinogenesis. 12 Based on the presented data, this study aimed to investigate the HPV infection spectrum, to identify the most prevalent genotypes, to determine the frequencies of SNPs Arg72Pro and MDM2 SNP309, and their association with possible risk factors for viral persistence and for the development of pre-neoplastic and neoplastic lesions of the uterine cervix in HIV-infected women.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible that genes that undergo selection in the TP53 pathway may affect human reproduction [29]. The G allele of MDM2 c.14+309T>G SNP is associated with a high risk of spontaneous abortion [16], which supports the combined effect between this MDM2 polymorphism and R72P of p53 [7,58]. The MDM4 gene, that is structurally homologous with the MDM2 gene, is also involved in the regulation of p53.…”
Section: Discussionmentioning
confidence: 78%
“…To this, for the first time in a TP53 negative Italian population of LFS Suggestive patients classified according to the revised Chompret criteria [7], we evaluated the effect of TP53 codon 72 polymorphism, MDM2 SNP309 and MDM2 SNP285 already described as putative genetic determinants in tumour onset, though with debatable results [16,17,34]. In particular, TP53 Pro72Arg has been controversially linked to cancer risk in different studies [14][15][16][17] but its role on TP53-negative patients has never been investigated. The MDM2 SNP309 has been shown to be a modifier factor in TP53 positive LFS patients, but only one previous study [19] focused the attention on a TP53 negative combined Dutch-Finnish population.…”
Section: Discussionmentioning
confidence: 98%
“…Meta-analyses studies on patients with various tumour types demonstrated that the Pro-Pro genotype is associated with an increased risk of carcinogenesis [16,17]; moreover Khan et al [17] found this effect related to the ethnicity. As a matter of fact, an increased risk of Pro-Pro genotype on cancer susceptibility had been evaluated in TP53 mutation carriers by many studies, but its role in a TP53 negative LFS case study has never been considered.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation